POLITICAL STABILITY IN ASIA PACIFIC - irwita Erlangga (Yogyakarta State University, 2018)
This paper aims to explore the dynamics of competition in the Asia Pacific region. The analysis in this article used a qualitative approach based on secondary data. The data collected from the official reports and other relevant sources. The findings showed that there is instability in intrastate politics, it does not have much effect on regional political constellations. Geopolitical and geo-economic shifts in the region are ongoing so it is natural that there is a process of adaptation that creates a bit of friction with domestic politics. Economy and military serve as a power base for superpowers to be able to spread its influence in a minor power state. However, the power of the superpower is not always constant. The tide of the presence of force can affect the political constellation of the region and lead to changes in hegemony.